Intravenous lipomas of head and neck: an exceptional entity and its clinical implications - Fernández-Alvarez, Verónica; Linares-Sánchez, Miriam; Mäkitie, Antti A.; Suárez, Carlos; de Bree, Eelco; Karatzanis, Alexander; Takes, Robert P.; Strojan, Primoz; Rinaldo, Alessandra; Ferlito, Alfio (Frontiers in Neurology, 2024)
Intravenous lipomas (IVLs) of the head and neck are uncommon benign tumors that develop within the venous walls, often detected incidentally during imaging for unrelated issues. While usually asymptomatic, these IVLs can cause congestive venous symptoms like swelling, paresthesia or pain in the head and neck and upper limbs, or even venous thromboembolism. The precise diagnosis of IVLs is predominantly achieved through computed tomography (CT) and magnetic resonance imaging (MRI), with CT being the most frequently used method. Symptomatic patients generally undergo open surgery with excision of the IVL followed by venous reconstruction, which has shown safe and effective outcomes. However, the management of asymptomatic IVLs remains controversial due to the limited number of reported cases. Despite this, there is a notable trend toward recommending surgical removal of IVLs to prevent complications and rule out malignancy, driven by the challenges of differentiating IVLs from malignant tumors using imaging alone. This review highlights the key differential imaging characteristics of IVLs and the main surgical techniques to remove the tumor and repair the vascular defect. Further research is necessary to establish a robust, evidence-based approach for treating asymptomatic IVLs, balancing the risks of surgery against the potential for future complications.